Parental Physical Punishment “Discipline” to Children and Adolescents: A Systematic Literature Review - Devi Maya Arista Devi; Nidya Comdeca Nurvitriana; Karunia Wijayanti; Andari Wuri Astuti (Journal of Research in Midwifery and Healthcare, 2025)
There are several intense discussions in the literature regarding the effectiveness of using physical punishment to discipline children, as well as its impact on the development of aggressive behaviors in children and adolescents. This literature review aims to investigate literature related to the use of physical punishment on children and the associated impact of physical punishment on child behavior development. A total of 10 articles were selected using PRISMA flowchart from relevant databases: PubMed, ScienceDirect, and Cochrane based on inclusion criteria. The literature indicates that physical punishment by parents is significantly associated with various child behaviors. It causes children to experience long-term depression until adolescence and adulthood. Additionally, the review suggests that children who experience physical punishment at home may suffer negative consequences at school. The research findings emphasize the importance of opposing the use of physical punishment as disciplinary method by parents and increasing awareness of the negative effects.